Cultural Sustainability of Hoi an Ancient Houses in the process of becoming the World Cultural Heritage City - Van, Nguyen Thi Bich; Singyabuth, Supachai (International Journal of Membrane Science and Technology, 2023)
In the face of increasing pressures of development towards industrialization and modernization, Hoi An ancient town, needs to add more research to preserve and sustainably promote the value of its cultural heritage. However, there are few studies on cultural sustainability in Hoi An ancient house architecture. Therefore, one of the research objectives of this article is to fill this gap by enhancing current knowledge in the field. The structure of this article explains the relationship between heritage value and ancient heritage houses, as well as the place and role of cultural sustainability in the overall framework of sustainable development. An in-depth literature analysis was conducted following a survey of five ancient houses in Hoi An to achieve these goals. This article also studies the cultural sustainability of ancient houses to solve problems in line with the orientation of Hoi An as an eco-cultural-tourism city